ASSESSMENT OF HEALTHCARE WORKERS’ KNOWLEDGE AND ATTITUDES REGARDING PPE USAGE, INCLUDING BARRIERS AND FACILITATORS TO COMPLIANCE WITH RECOMMENDED GUIDELINES IN NISHTAR HOSPITAL MULTAN - YASMIN , R; MAJEED , S; FAIZ , N; RASHID , SA (Biological and Clinical Sciences Research Journal, 2024)
Personal protective equipment (PPE) is a critical component of infection prevention and control, particularly in resource-limited healthcare settings like Pakistan. Compliance with PPE guidelines depends on healthcare workers’ (HCWs) knowledge, attitudes, and the systemic barriers and facilitators they encounter. Objective: To assess HCWs’ knowledge and attitudes regarding PPE usage, identify barriers and facilitators to compliance, and propose targeted interventions for improving adherence to PPE guidelines at Nishtar Hospital Multan. Methods: This descriptive cross-sectional study included 250 HCWs selected through simple random sampling. Data were collected using a structured, pre-tested questionnaire covering demographic details, knowledge and attitudes about PPE, and perceived barriers and facilitators to compliance. Statistical analysis was performed using IBM SPSS version 26, with results presented as frequencies and percentages. Chi-square tests were used to evaluate associations, with a p-value ≤0.05 considered significant. Results: Most participants (75%) correctly identified all PPE components, while 68% demonstrated adequate knowledge of proper donning procedures. Approximately 85% of HCWs recognized PPE as essential for infection control, but 60% found its usage inconvenient. The primary barriers to compliance were lack of training (60%) and limited availability (40%), while key facilitators included regular training programs (72%), accessible PPE supplies (80%), and strong leadership support (64%).Conclusion: Significant knowledge gaps and systemic barriers to PPE compliance were identified among HCWs at Nishtar Hospital. Improving training programs, ensuring consistent PPE availability, and fostering leadership engagement are essential steps toward enhancing compliance and strengthening infection control practices in resource-constrained settings.